2008
DOI: 10.1016/j.solmat.2008.06.012
|View full text |Cite
|
Sign up to set email alerts
|

Highly durable inverted-type organic solar cell using amorphous titanium oxide as electron collection electrode inserted between ITO and organic layer

Abstract: An indium tin oxide/titanium oxide/[6,6]-phenyl C 61 butyric acid methyl ester: regioregular poly(3-hexylthiophene)/poly(3,4-ethylenedioxylenethiophene): poly(4-styrene sulfonic acid)/Au type organic solar cell (ITO/TiO x /PCBM:P3HT/PEDOT:PSS/Au) with 1 cm 2 active area, which is called "inverted type solar cell", was developed using an ITO/amorphous titanium oxide (TiO x ) electrode prepared by a sol-gel technique instead of the low functional electrode such as Al. The power conversion efficiency (η) of 2.47 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
134
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 165 publications
(137 citation statements)
references
References 26 publications
0
134
0
Order By: Relevance
“…We recently reported that the ITO/ TiO x / PCBM:P3HT/PEDOT:PSS/Au type solar cells maintained the performance even under light irradiation for 20 h in an ambient atmosphere. 12 That is, the photodegradation of the PCBM:P3HT bulk is not responsible for increasing the R2 of the ZnS cell or for lowering of the performance in this time scale. This suggests that the charge transport between the ZnS and PCBM:P3HT layers became gradually difficult with light irradiation perhaps because of a photocatalytic effect.…”
Section: B Zns/bulk-heterojunction Interface Characterized By Alternmentioning
confidence: 97%
See 1 more Smart Citation
“…We recently reported that the ITO/ TiO x / PCBM:P3HT/PEDOT:PSS/Au type solar cells maintained the performance even under light irradiation for 20 h in an ambient atmosphere. 12 That is, the photodegradation of the PCBM:P3HT bulk is not responsible for increasing the R2 of the ZnS cell or for lowering of the performance in this time scale. This suggests that the charge transport between the ZnS and PCBM:P3HT layers became gradually difficult with light irradiation perhaps because of a photocatalytic effect.…”
Section: B Zns/bulk-heterojunction Interface Characterized By Alternmentioning
confidence: 97%
“…[7][8][9][10][11] For example, we reported that the ITO/amorphous TiO x / PCBM:P3HT/PEDOT:PSS/Au inverted type cell showed the power conversion efficiency of 2.47% and the performance of the cells with sealing was about the same after continuous light irradiating for 120 h in an ambient atmosphere. 12 Even without sealing, this solar cell maintained the performance after continuous light irradiation for 20 h. Thus, we have the techniques required to fabricate the organic thin-film solar cells with reasonable performance and stability.…”
Section: Introductionmentioning
confidence: 99%
“…The ZnPc was added as the third component for PCBM:P3HT solar cells. The polarity of charge collection is reversed from conventional devices in the inverted structure [22][23][24], which are expected to provide stable devices in air [25][26][27][28]. The photovoltaic mechanism and charge transfer were discussed on the basis of light-induced current density-voltage (J-V) curves and IPCE.…”
Section: Introductionmentioning
confidence: 99%
“…[11] This structure is a promising candidate for further studying polymer solar cell durability improvement. [12][13][14] PET-ITO substrates (sheet resistance = 30 Ω/sq., thickness of PET sheet = 125 µm) were obtained from Nakai Industrial Co., Ltd.…”
Section: Introductionmentioning
confidence: 99%